Medea Rejuvenates Herself: Female Roles and the Use of the Body in Seneca’s Medea - Ildikó Csepregi (Clotho)
The aim of this paper is to illustrate the arc of the sequence of events through which Medea rejuvenates herself – as she has rejuvenated others before her, she does it as if she were simply disassembling herself and putting herself in her own cauldron to be reborn as her younger and stronger self. After describing the different and changing female roles of Seneca’s Medea, the paper gives a close reading of the text to show how Seneca uses images of the body and to underscore the way Medea uses her own body to achieve her transformation: to start a new life by returning to her earlier self, i.e., by rejuvenating herself. To back this argument, the paper also highlights her previous acts of rejuvenation in textual and pictorial testimonies and argues that Seneca presented Medea as a rather positive figure, a deity, a magician, a healer, who is capable of ruling over life and death.